Gratification Disorder Associated With Perineal Irritation in Young Children: Management and Short-Term Outcome. Issue 3 (July 2021) - Moktan, Sherina; Karki, Utkarsh; Bista, Isha; Devkota, Narmada
Masturbatory behaviors occur as a part of psychosexual development in young children, but if such behaviors exceed resulting in discomfort and disability, it is known as gratification disorder. Children with such genital self-stimulatory behaviors are infrequently seen and diagnosed in Asian outpatient settings, possibly due to prevalent stigma. We report the cases of 3 children of 3, 4, and 8 - year-old with the diagnosis of gratification disorder based on comprehensive history-taking, general physical examination, and neurological examination along with videotape recording of the event. Investigations such as electroencephalogram (EEG), urinary microscopic examination, and culture were also conducted in each case. Clinical history, examination, and investigations such as EEG and urinary examination were reviewed. Behavior therapy and psychoeducation were successful in alleviating the disorder and allaying parental fears of taboo in all these cases. There was significant improvement in self-genital stimulatory behavior in all 3 cases at 3 months follow-up.